One-pot synthesis of sorbitol via hydrolysis-hydrogenation of cellulose in the presence of Ru-containing composites. (January 2021) - Gromov, Nikolay V.; Medvedeva, Tatiana B.; Rodikova, Yulia A.; Timofeeva, Maria N.; Panchenko, Valentina N.; Taran, Oxana P.; Kozhevnikov, Ivan V.; Parmon, Valentin N.
Graphical abstract: Highlights: Cellulose hydrolysis-hydrogenation into sorbitol sweetener is studied. Ru-containing composites of H3 PW12 O40 with ZrO2 or Nb2 O5 were bifunctional catalysts. Activation temperature of supports influences the catalytic activity. 3%Ru-PW/ZrO2 are more active compared to 3%Ru-PW/Nb2 O5. Sorbitol yield reaches 66% over 3%Ru-PW/ZrO2 when the support activated at 550 °C. Abstract: The aim of this work was to study the one-pot synthesis of sorbitol via hydrolysis-hydrogenation of cellulose in the presence of Ru-containing composites based on H3 PW12 O40 supported on ZrO2 and Nb2 O5 (Ru-PW/ZrO2 and Ru-PW/Nb2 O5 ). The main parameters impacted the reaction rate and yield of sorbitol, i.e. reaction conditions and type of catalyst were investigated. Ru-PW/ZrO2 systems were more active than Ru-PW/Nb2 O5 . The yield of sorbitol was found to depend on the activation temperature of PW/ZrO2 and PW/Nb2 O5 which affected textural properties, the amount of acid sites and size of Ru nanoparticles. The highest 66% sorbitol yield was observed in the presence of 3%Ru-PW/ZrO2 activated at 550 °C and 1/1 of weight ratio of cellulose/catalyst, 180 °C, 7 MPa hydrogen pressure. This catalyst was stable for three cycles of the reaction without lost of it's activity.